Pengaruh Zakat Online terhadap Efisiensi dan Transparansi Dana Zakat di Badan Amil Zakat Nasional (BAZNAS) Kota Semarang - Miftahudin; Umam, Mirzalul; Hidayat, Alfian (Journal of Applied Islamic Economics and Finance, 2024)
This research was conducted with the aim of contributing to the understanding of the role of online zakat and analyzing the influence of online zakat on the efficiency and transparency of zakat fund management at BAZNAS Semarang City in improving the quality of service and encouraging community participation in conducting zakat online. This research uses a combination of qualitative and quantitative research. Data was obtained through interviews with informants at BAZNAS Semarang City, analysis of zakat fund management documents, and observation. The results of this research show that online zakat is 100% efficient as demonstrated by DMU (decision making unit) with a score and benchmark of 1 so that input factors are managed to produce output, namely zakat funds are collected and distributed optimally. Online zakat also increases the transparency of zakat fund management through: Clear Reporting, Accessibility of Information, Clear Use of Funds, Management Efficiency, and Use of Technology that makes it easier for muzaki and mustahik.